Echocardiographic findings in young adults with primary hypertension: A scoping review protocol - Lyana Shahirah Mohamad Yamin; Maryam Alsharqi; Mohd Asyiq Al-Fard Mohd Raffali; Akmal Sabarudin; Afifah Binti Mohamed (PLoS ONE, 2025)
Echocardiography is the primary imaging tool for evaluating cardiac structure and function in patients with primary hypertension. A significant limitation of the current literature is that most studies focus on older adults, leaving a significant gap in understanding the cardiac effects of primary hypertension in young adults. This scoping review protocol aims to assess conventional echocardiographic parameters, left ventricular geometric patterns, and advanced echocardiographic findings for the early detection of cardiac changes in young adults aged 18–39 with primary hypertension. A systematic literature search will be conducted across the MEDLINE, EMBASE, Web of Science, Scopus, and Cochrane Central databases. This involves systematically reviewing existing literature to outline the reported echocardiographic findings, the parameters analysed, and the abnormalities identified within this population. It will establish the foundation for future reviews and primary research, supporting the evaluation of the diagnostic and prognostic significance of these findings for early detection and risk assessment, ranging from standard conventional measures to more advanced methods.